Needs Analysis of Islamic Religious Education Teaching Materials Integrating Local Wisdom at Universitas Negeri Gorontalo - Agil Bahsoan; Abdul Haris Panai; Nur Mohamad Kasim; Mohamad Zubadi; Novianty Djafri; Tuti Wantu (PPSDP International Journal of Education, 2026)
This study aims to identify and analyze the needs for developing Islamic Education (IRE) teaching materials that incorporate local wisdom at Gorontalo State University. The study uses a descriptive quantitative approach through the distribution of questionnaires to students taking IRE courses, with the aim of exploring their perceptions and needs regarding the integration of cultural activities and regional cultural values, especially those of Gorontalo, into the learning process. This study uses a descriptive quantitative approach through a needs analysis of 50 students at Universitas Negeri Gorontalo who are enrolled in Islamic Religious Education courses for the 2025/2026 academic year, with the aim of identifying the urgency of developing IRE teaching materials based on local wisdom. The results of the analysis show that students have a high level of awareness and strongly support the importance of applying Gorontalo cultural values in teaching materials. These values are considered capable of deepening religious understanding, strengthening moderate attitudes, and shaping a religious and cultured social character. These findings confirm that IRE teaching materials need shift from textual learning to contextual and constructivist learning, so that Islamic teachings can be more easily understood, internalized, and applied in students’ lives. The results of this study provide a basis for educators and curriculum developers to design teaching materials that are in line with the local socio-cultural context. Further research is recommended to develop and test teaching materials based on local wisdom using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model to assess their effectiveness in strengthening religious moderation and cultural identity among university students.